Application of pirarubicin photosensitizer fluorescence cystoscopy in early detection of bladder cancer - Jiang, Bo (Oncol Lett, 2017)
The aim of this study was to investigate the value of pirarubicin (THP) photosensitizer fluorescence cystoscopy for the early diagnosis of bladder cancer. From January 2012 to June 2015, 25 patients with painless gross hematuria, were injected with THP 15 min prior to surgery and subsequently underwent fluorescence cystoscopy examination. Locations of tumors were recorded and biopsies were performed (total of 109 biopsies) under white and fluorescence light guidance. Biopsies were conducted at the THP-positive and -negative areas under white light and THP-positive areas under fluorescence light. Positive rate of bladder tumor tissue at the THP-positive areas detected under fluorescence light was 92.86%. The sensitivity and specificity were 100 and 96.15%, respectively. The positive rate of tumor tissue at the THP-positive areas detected under white light was 70.97%. The sensitivity and specificity were 100 and 84.74%, respectively. Fifty biopsies taken at the THP-negative areas under white light were found to be non-urothelial carcinoma tumor lesions. Thus, applying (THP) photosensitizer fluorescence cystoscopy for early-period bladder cancer diagnosis is safe, effective and practical. It showed a high degree of specificity and a low rate of false positives. It was a convenient visual diagnostic method for the early detection of non-muscular invasive bladder cancer.